PERAN SATPOL PP DALAM PENERTIBAN JAM OPERASIONAL WARNET DI KOTA PEKANBARUTAHUN 2018 - Ruari, Syahran; Asrida, Wan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research is motivated by the Controlling of entertainment venues, so that there are no deviations committed by entertainment venues in the District of Tampan, Pekanbaru City, especially internet cafes. Pekanbaru City Civil Service Police Unit as Enforcement of Regional Regulation must work optimally for the implementation of Pekanbaru City Regulation No. 3 of 2002 concerning General Entertainment. In controlling the internet cafes, which are indicated to violate regulations related to Perda No. 3 of 2002, it is necessary to have approaches to control the internet cafes in a professional manner and not violate the applicable rules including through the process of persuasive, preventive and repressive action (task) approaches Problem formulation in this research, namely how the Civil Service Police role in controlling operational hours of entertainment (warnet) in Tampan District, Pekanbaru City. The research method used is descriptive qualitative method with data collection instruments including interviews, documentation studies related to research objectives. The results of the study illustrate that the role of the Satpol PP Pekanbaru City must be increased again in carrying out the duties, responsibilities and applicable SOPs. Included in the regulation of internet cafes entertainment places that violate Regional Regulation No. 3 of 2002 concerning Public Entertainment. There is a need for special attention in the implementation of policies that must be made or issued by the city and provincial governments related to material and non-material support to the Satpol PP Pekanbaru City, so that Perda No. 3 of 2002 can run optimally. Factors such as persuasive, preventive and repressive tasks or actions that affect the role of the Pekanbaru City Satpol PP are considered not effective in carrying out the duties of the Pekanbaru City Civil Service Police Unit in accordance with Bylaw No. 03 of 2002, so that controlling public places for internet cafes in Tampan District, Pekanbaru City is not optimal Keywords: Persuasive Actions, Preventiv, Repressive.